Effect of Residential Yoga Camp on Psychological Fitness of Adolescents: A Cohort Study - Astha Choukse; Amritanshu Ram; HR Nagendra (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Discovering and promoting ways that improve adolescents’ psychological fitness has been a recurrent concern in the field of health and psychology. Adolescence, as a period of transition, is highly prone to have mental health risks and unhealthy behaviour patterns. Thus, it is the right time to promote healthy practices to prevent problems of health and behaviour in adulthood. As Yoga provides practical solutions for mental health, we anticipated that exposure to it should improve psychological fitness among adolescents. Aim: To evaluate the effectiveness of short term residential yoga intervention on psychological constructs in adolescents. Materials and Methods: A pre, post-yoga interventional study was carried out in a 10 day residential camp. Three independent cohorts of adolescents from India, in three batches (1, 2 and 3), with sample size of 148 (87 boys and 61 girls), 167 (122 boys and 45 girls) and 195 (121 boys and 74 girls), respectively were examined. A holistic integrated yoga module with eight hours of yoga sessions per day was given as an intervention. Emotional Intelligence (EI), emotional regulation strategies, Clinical anger and self-concept parameters were studied using psychometric scales like Schutte Emotional Intelligence Scale (SEIS), Cognitive Emotion Regulation Questionnaire (CERQ-short), Clinical Anger Scale (CAS) and Self-concept Scale respectively. Authorised scales and software were used for assessments and analyses. Results: Significant (p<0.05) improvements in EI, emotional regulation and anger management were observed in all the three batches. However, no significant improvement was found in self-concept in either of the cohorts. The observation of the results of assessed outcome measures in all the three batches confirms the positive effect of Yoga intervention on psychological fitness. The pattern of changes was consistent across all three batches. Conclusion: Residential Yoga camp improves the psychological fitness among adolescents. Even short term courses are effective and induce positive behavioural signatures.